La teoría de los conjuntos-T aplicada al desarrollo de la competencia de modelado matemático - De Armas-Costa, Ricardo Joaquin; Macías-Mora, David; Bernal-Bueno, Ricardo (Revista Científica, 2016)
In this article we want to present parts of the theory of joint-T and how it is applied in higher education to develop the competence of mathematical modeling subjects. We explain how the theory can develop the skills of students. This theory is a response to the problems of learning of mathematics that originate in the curriculum designed to acquire information and not only to develop the math skills of students.